Pelatihan Model Pembelajaran Kooperatif (Cooperative Learning) Bagi Tutor Paud Pada Masa Pandemi di Kecamatan Cipayung Jakarta Timur - Yasmin Faradiba; Yudrik Jahja; Hikmah; Yayah Tika (Publikasi Indonesia, 2022)
PAUD teachers during a pandemic have potential environmental support that can be useful for Cooperative Learning. However, PAUD teachers during the pandemic have not been able to understand the concept of Cooperative Learning nor have they been able to properly contain the concept of Cooperative Learning and have difficulties in implementing it. Based on this condition, the implementation of Community Service (P2M) is in the form of learning training using Cooperative Learning. This activity is in the form of training with methods used online, semi-workshops and practical in this P2M activity, PAUD tutors are given understanding, training and assistance regarding Cooperative Learning aimed at increasing understanding and application of Cooperative Learning in learning. The expected result after this training is that there is a significant change in the learning competence of PAUD teachers by showing an increase in teachers' understanding of Cooperative Learning, as well as an increase in skills in learning using Cooperative Learning.